Quinoline-2-carboxlic acid derivatives bearing oxadiazole moiety: Synthesis, Skin Antitumor, ‎Antibacterial, antifungal activities, and POM studies for the Identification of the Pharmacophore ‎Sites - Ahamed, Luma S.; AL sahib, Sanaa A.; Ahmed, Rana S.; Al-khazraji, Shaima Ibraheem (Iraqi Journal of Science, 2025)
A new series of chalcone derivatives featuring an oxadiazole-quinoline moiety were successfully synthesized through a multi-step reaction sequence, commencing with quinoline-2-carboxylic acid as the starting material. First, the carboxylic group was chlorinated to form an acid chloride, following reacted with hydrazine hydrate. The resulting product underwent cyclization with carbon disulfide in an alkaline solution to produce 5-(quinolin-2-yl)-1,3,4-oxadiazole-2-thiol, followed by alkylation using chloroacetone. In the final step, an aldol condensation reaction was carried out by grinding the acetone derivative with various aromatic aldehydes, yielding the desired chalcones. The synthesized compounds were characterized by Rf, FTIR, 1HNMR, and 13CNMR. The effects of compound S6 were evaluated using an MTT assay. This assay was performed on two cell lines - the skin cancer cell line A375 and the normal cell line HdFn (human dermal fibroblasts) which performed a significant inhibition rate. All synthesized compounds were evaluated against four different types of bacteria like S. aureus, streptococcus epidermidis, E.coli, Klebsiella spp. and one type of fungi like Candida albicans. Additionally, (Petra/Osiris/Molinspiration) POM analyses were utilized to identify pharmacophore sites for the newly synthesized compounds.